Trade and Aid : Eisenhower's Foreign Economic Policy, 1953-1961 - Kaufman, Burton Ira (Book collections on Project MUSE., 2019)
This book outlines the transition of U.S. foreign policy during the Eisenhower administration. In the years leading up to Eisenhower's election, America's predominant foreign economic program was based on the concept of "trade not aid," which deemphasized foreign aid and relied instead on liberalized world trade and the encouragement of private foreign investment to assure world economic growth. When Eisenhower took office in 1953, he embraced this doctrine. However, as problems in the Third World worsened, it became clear to Eisenhower and other architects of American foreign policy that trade and private investment were insufficient solutions to the economic woes of developing nations. In 1954 Eisenhower began to embrace economic aid as a core axis of his foreign economic policy. Burton I. Kaufman contextualizes Eisenhower's foreign policy leadership in the ongoing historical evaluation of Eisenhower's leadership prowess. He evaluates the outcomes of the Eisenhower administration's trade and aid program, arguing that developing countries were worse off by the time Eisenhower left office.